The effects of relaxation therapy among head and neck cancer patients on quality of life - Johari, Siti Nor Ashiah (2021)
Objectives Head and neck cancer (HNC) is a debilitating condition due to the impact of the cancer and its treatment consequences on the daily basic-life function namely breathing, speech and swallowing. Hence, HNC has been detrimental to the patients, leading to an adverse impact on their quality of life (QoL). The objective of our study was to study the effect of relaxation therapy among head and neck cancer patients on QoL. Specifically, the study aimed to determine changes in anxiety, depression and quality of life score within relaxation therapy and psychoeducation therapy group. It also compared differences in anxiety, depression and quality of life score between relaxation therapy and psychoeducation group at pre- and post-intervention. Methods A randomized clinical trial was conducted. HNC patients were recruited from Otorhinolaryngology (ORL) clinic and Oncology clinic. They were randomly grouped into study and control groups. The study group received periodically-time-specific relaxation therapy at week 1,2,4 and 6 at Psychiatric Rehabilitation Center @Mentari USM, whereas the control group were provided with psychoeducation at week 1 and 6. The evaluations were done at week 1 (before commencement of therapy) and week 6 (after completion of intervention) using Functional Assessment Cancer Therapy-Head & Neck (FACT-H&N version 4) questionnaires for assessment of QoL, and Hospital Anxiety and Depression Scale (HADS) for screening of anxiety and depression. Results A total of 26 participants were recruited for this study. There was statistically significant reduction (p-value=0.041) in the level of depression after relaxation therapy at 6-week period. The subscale of SWB and EWB showed improvement in scoring after the relaxation therapy, but not statistically significant (p-value>0.050). There was no statistically significant reduction in the level of anxiety and overall improvement of the QoL after relaxation therapy at 6-week period. Conclusions In conclusion, the study suggests that the relaxation therapy showed statistically significant reduction in depression level and have a beneficial outcome among HNC patients in managing the psychological distress that later potentially contribute to better QoL. Therefore, the relaxation therapy can be emphasized as an adjunct therapy as part of holistic approach among HNC patients’ management.